Five‐year relative survival for human papillomavirus‐associated cancer sites. Issue 1 (6th November 2017) - Razzaghi, Hilda; Saraiya, Mona; Thompson, Trevor D.; Henley, S. Jane; Viens, Laura; Wilson, Reda
Abstract : BACKGROUND: Human papillomavirus (HPV) vaccines can potentially prevent greater than 90% of cervical and anal cancers as well as a substantial proportion of vulvar, vaginal, penile, and oropharyngeal cancers caused by certain HPV types. Because more than 38, 000 HPV‐associated cancers are diagnosed annually in the United States, current studies are needed to understand how relative survival varies for each of these cancers by certain demographic characteristics, such as race and age. METHODS: The authors examined high‐quality data from 27 population‐based cancer registries covering approximately 59% of the US population. The analyses were limited to invasive cancers that were diagnosed during 2001 through 2011 and followed through 2011 and met specified histologic criteria for HPV‐associated cancers. Five‐year relative survival was calculated from diagnosis until death for these cancers by age, race, and sex. RESULTS: The 5‐year age‐standardized relative survival rate was 64.2% for cervical carcinomas, 52.8% for vaginal squamous cell carcinomas (SCCs), 66% for vulvar SCCs, 47.4% for penile SCCs, 65.9% for anal SCCs, 56.2% for rectal SCCs, and 51.2% for oropharyngeal SCCs. Five‐year relative survival was consistently higher among white patients compared with black patients for all HPV‐associated cancers across all age groups; the greatest differences by race were observed for oropharyngeal SCCs among those aged <60 years and for penile SCCs among those ages 40 to 49 years compared with other age groups. CONCLUSIONS: There are large disparities in relative survival among patients with HPV‐associated cancers by sex, race, and age. HPV vaccination and improved access to screening (of cancers for which screening tests are available) and treatment, especially among groups that experience higher incidence and lower survival, may reduce disparities in survival from HPV‐associated cancers. Cancer 2018;124:203‐211. Published 2017. This article is a U.S. Government work and is in the public domain in the USA. Abstract : Five‐year relative survival is highest for patients who have vulvar and anal cancers and lowest for those who have penile and oropharyngeal cancers compared with other human papillomavirus‐associated cancers. There are large racial disparities in survival in which higher survival is consistently observed for whites compared with blacks. See also pages 18‐20.